Determining the relative validity and reproducibility of a food frequency questionnaire (FFQ) to assess nutrient intake in older adults living in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Yu, Angela Dawn (Massey University, 2019)
Background: New Zealand’s population is ageing. Dietary intakes in older adults and physiological changes through ageing are important predictors of health and disease outcomes. However, it is challenging to capture the typical diet of older adults. Among different types of dietary assessment tools, a food frequency questionnaire (FFQ) is easy to administer and causes less burden to participants. To the best of our knowledge, the latest FFQ validation study in older adults was undertaken nearly 30 years ago. A valid and reproducible FFQ to measure multiple nutrients intake in older New Zealanders is warranted. Aim: This study aims to assess the validity and reproducibility of an FFQ designed to measure a range of relative nutrient intakes in older adults aged 65 to 74 years in New Zealand. Methods: As part of the Researching Eating, Activity and Cognitive Health (REACH) study, a convenience sample of community-dwelling older adults 65 to 74 years were recruited for a cross-sectional observational study. Participants (n = 166) who completed a 109-item FFQ to assess dietary intakes over the past month and a four-day food record (4DFR) were included in the validity analysis; participants (n = 319) who completed the FFQ and re-administered FFQ four weeks later were included in the reproducibility analysis. Energy intake was adjusted for nutrients in the statistical methods. Relative validity and reproducibility of the FFQ were assessed using paired t-tests, Pearson’ or Spearman’s correlation coefficients, cross-classification with weighted kappa statistics, Bland-Altman plots, and linear regression analysis for energy and 28 nutrients. Results: Energy adjustment caused moderate improvements on both validity and reproducibility. The validity correlations for energy adjusted nutrient intakes ranged from 0.05 (selenium) to 0.76 (alcohol), with a mean of 0.35. Validity correlations above 0.40 were observed for 12 nutrients after energy adjustment, including carbohydrate, sugar, dietary fibre, total fat, monounsaturated fat, polyunsaturated fat, cholesterol, vitamin E, calcium, and magnesium. At least 50% of participants were correctly classified into the same tertiles for nine nutrients. Less than 10% of participants were grossly misclassified into the opposite tertiles for seven nutrients. Weighted kappa values for validity demonstrated fair agreement (ĸ 0.21-0.40) for 19 nutrients and good agreement (ĸ >0.61) for alcohol intake. Reproducibility correlations for energy adjusted nutrients ranged from 0.30 (vitamin A) to 0.91 (alcohol), with most nutrients (n = 25) falling between 0.60 and 0.80. For reproducibility, the mean correct classification was 60%, ranged between 53 and 78%. Gross misclassification for energy adjusted nutrients ranged from 0.6 to 7.8%. Weighted kappa values for reproducibility demonstrated moderate agreements (ĸ 0.41-0.60) for 25 energy adjusted nutrients and good agreement (ĸ >0.61) for alcohol. Conclusion: The FFQ showed reasonable relative validity for ranking nutrient intakes in older New Zealanders 65-74 years old. The FFQ appears to have good reproducibility for assessing energy and nutrient intakes. The FFQ could be used in future research for relative nutrient assessments in older adults but is not suitable for measuring absolute nutrient intakes.
Keywords: Older people; Nutrition; New Zealand; Evaluation; Nutrition surveys; ageing; elderly; reliability; validation; food diary; dietary questionnaire; macronutrient; micronutrient; 321004 Nutritional science